1954
DOI: 10.1111/j.2153-3490.1954.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of the Flow of Stratified Fluids: II. Experiments with a Two-Fluid System

Abstract: A description is given of the flow of two superimposed layers of fluid over a barrier. This represents a partial experimental investigation of a problem considered theoretically in Part I. In general three regimes of motion are possible: If the velocities of the fluids are sufficiently small the interface is little disturbed except for a slight depression over the barrier. If the velocities are sufficiently high the interface swells symmetrically over the obstacle. At intermediate speeds a hydraulic jump occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

1968
1968
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 9 publications
(3 reference statements)
5
97
0
Order By: Relevance
“…For a straight channel, i.e. D c = 1, Equation (4) reduces to the simpler form for a onedimensional flow over an infinitely long ridge (Long, 1954). Using data for the Zagreb profile at 12 UTC from Table II for the far-upstream condition, we derive M c = 0.37, based on F ∞ = 0.3 and D c = 1.…”
Section: Upstream Profilementioning
confidence: 99%
“…For a straight channel, i.e. D c = 1, Equation (4) reduces to the simpler form for a onedimensional flow over an infinitely long ridge (Long, 1954). Using data for the Zagreb profile at 12 UTC from Table II for the far-upstream condition, we derive M c = 0.37, based on F ∞ = 0.3 and D c = 1.…”
Section: Upstream Profilementioning
confidence: 99%
“…The ultimate understanding of such complicated flows will require reference to idealized models in which generic transients can be isolated and studied. In non-rotating hydraulics, Long's towing experiments (Long 1954(Long , 1955(Long , 1970 and the classical dam break problem (Stoker 1957) have provided a foundation for investigating more complex phenomena. In geophysical fluid dynamics, the classical Rossby adjustment problem (see Gill 1982) and its extension to a channel setting (Gill 1976;Hermann, Rhines & Johnson 1989;Tomasson & Melville 1992) have played a similar role.…”
Section: Introductionmentioning
confidence: 99%
“…Long (1954) theoretically studied the behavior of shallow fluid over a mountain and compared it with laboratory experiments. He showed that there is a definite limit to the mountain height for the existence of the steady-state solution and that the behavior of the shallow fluid can be classified by the Froude number of the approaching flow and non-dimensional mountain height into three regimes: a sub-critical flow, an unsteady flow having hydraulic jumps, and a supercritical flow.…”
Section: Introductionmentioning
confidence: 99%